Correlation with the protection of the authority of criminal judging and social evaluation (Academic Journal of Internal Affairs, 2022)
Aim: The protection of the authority of the judges is especially relevant today, when the number of threats and other activities seem to be increasing in order to influence the judicial decisions as well as criticize severely the decisions already made by the judges. In addition to the critics of judgments which either go beyond the expression of opinion or not, derogatory, disparaging and defamatory statements occur very often insulting the judges and their work. The question is whether the available legal instruments are sufficient enough to take legal actions against these morally unacceptable or even illegal conducts. The aim of our study is to investigate and explore the relationships between the protection of the authority of criminal justice and social value judgements.Methodology: In addition to formulating thoughts and considerations from the field of the philosophy of law, our conclusions are based on the Act XC of 2017 on the Code of Criminal Procedure.Findings: We started from the basic statement that criminal case-law considered as a legal service to ensure law and order requires social acceptance. However, it can only be guaranteed if moral values and expectations were fulfilled and the “moral ideals” of the society were truly realized. To make it happen, the judge hearing a specific case sometimes should, remaining strictly within the legal framework, depart from the established and uniform case-law in order to adhere to the moral values he or she professes. It reflects partly the fact that courts do necessarily serve social policy goals as well.Value: We thrived to reveal the fact that public trust in the courts is a fundamental interest of both the courts themselves and the citizens. But to strengthen and deepen that trust certain efforts have to be made even by the judiciary. Everything must be done in order that courts can respond appropriately to the developments and changes in social conditions and needs but, from time to time, unique cases might as well emerge when the recognition that social critique actually reflects the critique of the law should be articulated more distinctively.
Keywords: authority; protection; judge(s); society